2010
DOI: 10.1021/la100125v
|View full text |Cite
|
Sign up to set email alerts
|

Solidification and Ordering during Directional Drying of a Colloidal Dispersion

Abstract: During drying, colloidal dispersions undergo processes such as solidification, cracking, and the draining of interstitial pores. Here we show that the solidification of polystyrene and silica dispersions, during directional drying, occurs in two separate stages. These correspond to the initial ordering, and subsequent aggregation, of the colloidal particles. Transitions between these stages are observed as changes in transparency and color that propagate as distinct fronts along the drying layer. The dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
137
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(158 citation statements)
references
References 28 publications
19
137
2
Order By: Relevance
“…11). These changes were expressed as drying fronts, which propagated across the film at some speed v, as have been previously reported [3, 4,12,30,31]. Observing at one point, the transitions were seen as occurring at different times, as the fronts successively passed through the beam.…”
Section: Discussion Three Transitionsmentioning
confidence: 66%
See 2 more Smart Citations
“…11). These changes were expressed as drying fronts, which propagated across the film at some speed v, as have been previously reported [3, 4,12,30,31]. Observing at one point, the transitions were seen as occurring at different times, as the fronts successively passed through the beam.…”
Section: Discussion Three Transitionsmentioning
confidence: 66%
“…The superficial fluid velocity should take a maximum, u 0 , at the aggregation front, and decrease slowly until stagnation at the pore opening front, over a distance, x d = vτ d . Assuming that x d is constant, then this mass balance is simply [12] …”
Section: The Solid Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral drying has been termed the coffee ring effect, after the original work by Deegan et al [5]. The lateral drying also results in pressure gradients and film cracking [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the larger 1 mm trace widths were observed to yield a change in the colour shade at the trace edges ( Figure 9). Goehring et al [54] reported on such a phenomenon in the drying of colloidal dispersions. In particular, they observed a series of fronts when a colloidal suspension dries directionally, with distinct regions separating the liquid dispersion and the solid film [54].…”
Section: Printability and Measurable Resistancementioning
confidence: 98%